2012
DOI: 10.1136/emermed-2012-201612
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of metronome sound guidance via a phone speaker during dispatcher-assisted compression-only cardiopulmonary resuscitation by an untrained layperson: a randomised controlled simulation study using a manikin

Abstract: Metronome sound guidance during DA-COCPR for the untrained bystanders improved the chest compression rates, but was associated more with shallow compressions than the conventional DA-COCPR in a manikin model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 37 publications
5
39
0
1
Order By: Relevance
“…16 There have been metronome-based studies illustrating improvement of adequate compression rate, but, unlike our study, they demonstrated a negative impact on the depth of chest compressions. 18,19 Our study focused on rate-only feedback from a metronome because it is easily accessible as part of the defibrillator machine on code carts and the defibrillators in the resuscitation room. The actual cause of suboptimal chest compression depth with metronome guidance is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 There have been metronome-based studies illustrating improvement of adequate compression rate, but, unlike our study, they demonstrated a negative impact on the depth of chest compressions. 18,19 Our study focused on rate-only feedback from a metronome because it is easily accessible as part of the defibrillator machine on code carts and the defibrillators in the resuscitation room. The actual cause of suboptimal chest compression depth with metronome guidance is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been hypothesized that various factors could contribute to shallower compressions, including multitasking, rescuer fatigue, and rescuer distraction (concentrating on rate management rather than maximal effort). [18][19][20] The effect of greater compression depth is associated with increased coronary perfusion pressure, higher success of defibrillation, increased cardiac output, and improved clinical outcomes. 21,22 A compression depth of 5 cm is more effective than 4 cm in children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…One study has specifically explored this and suggested that faster rates were associated with a reduction in the quality and depth of chest compressions (Hurst et al 2011). This is backed up by some evidence of a reduction in compression depth (Oh et al 2008, Chung et al 2012, Park et al 2013. The majority of studies have been performed in simulated clinical situations using manikins.…”
Section: Commentsmentioning
confidence: 99%
“…Among these key elements, chest compression depth was suboptimal in both groups. Most CPR simulation studies show that the quality of layperson performed chest compression rarely meets the recommended standard 12,13 , even with dispatch assistance 8, 14 . Studies showed that using simplified dispatch instruction for CPR to coach participants "push as hard as you can" could provide deeper compression when compared to standard CPR instructions, but the results of depth in these studies were still suboptimal 15 − 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Since this study was a pilot study, the sample size was set to about 30 in each group with reference to the previous studies 8, [12][13][14][15][16] .…”
Section: Statisticsmentioning
confidence: 99%